Paita Bay environmental assessment - Cabrera Carranza, Carlos (2005)
This present work makes part of the research project Environmental Evaluation and Recovery of the Bay of Paita, carried out in 2003 and sponsored by the High Research Council of the UNMSM. The present study has the aim of evaluating the environmental conditions of the Bay of Paita and its surrounding as well as to suggest solution strategies to the various environmental problems shown to improve populations’ life quality and to preserve environment and natural resources. Our conclusion is that there is impairment of both urban and physical environments, and activities incompatibility, which makes evident a lack of territorial ordering.